The effectiveness of existing policies and procedures in the admission of students with SEND in the UAE higher education - AL OBEIDLI, NOOREYA (2018)
Inclusion of students with special needs and disabilities (SEND) in the schools would prepare to gain their rights through smoother process to access the higher education. Including them in the schools raise the expectations to be included in the next education stage. The number of the students with SEND included in the schools and competing the high school is growing which will increase their demands to enter the higher education (Wolanin & Steele 2004). Higher education plays an important role in social and cultural development through responding to the changes in communities, and meets the requirements affectively (Chatterton & Goddard 2000). Completion of post-secondary education can help people with special needs and disabilities to get better job opportunities, which influences their life style positively and support their independence (Zatt, Hart, and Zimbrich, 2004). The main aim of this study is to explore existing admission process and services to support students with special education needs and disabilities (SEND), and examine the effectiveness of the policies and procedures on their admission and enrolment in both public and private universities in the United Arab Emirates (UAE). This qualitative research has used multiple methods such method as semi-structured interviews with individuals who are in positions to process students’ applications and make the admission decisions for the student with SEND in higher education. Document analysis was used as a tool to support the study such as policies, and procedures. Recruitment process, admission requirements and process, criteria to make the admission decision for SEND in the higher education were also examined. The main finding revealed an existing gap between what’s written in the policies and procedures and the real practice, especially in the public universities. This gap has direct implications for the students with SEND to get access to join the higher education. The study ends with recommendations to help the decision makers in future practices.